2012
DOI: 10.1242/jcs.104174
|View full text |Cite
|
Sign up to set email alerts
|

Rab-genome analysis reveals novel insights in Weibel-Palade body exocytosis

Abstract: SummaryWeibel-Palade bodies (WPBs) are endothelial-cell-specific organelles that, upon fusion with the plasma membrane, release cargo molecules that are essential in blood vessel abnormalities, such as thrombosis and inflammation, as well as in angiogenesis. Despite the importance of WPBs, the basic mechanisms that mediate their secretion are only poorly understood. Rab GTPases play fundamental role in the trafficking of intracellular organelles. Yet, the only known WPB-associated Rabs are Rab27a and Rab3d. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 77 publications
2
96
0
7
Order By: Relevance
“…Their experiments further showed that Munc13-4, an already known effector of Rab27a, colocalized with Rab15 at WPBs. Taken together, this information suggests that the three proteins Rab27a, Rab15, and Munc13-4 likely work in tandem to help regulate exocytosis of vWF (Zografou et al, 2012). -CaM further binds to the amino terminus of Ral GDS, which leads to the dissociation from the inhibitory beta-arrestin and to activation of RalA.…”
Section: A Components Of Exocytosis Signaling Microdomainsmentioning
confidence: 93%
See 2 more Smart Citations
“…Their experiments further showed that Munc13-4, an already known effector of Rab27a, colocalized with Rab15 at WPBs. Taken together, this information suggests that the three proteins Rab27a, Rab15, and Munc13-4 likely work in tandem to help regulate exocytosis of vWF (Zografou et al, 2012). -CaM further binds to the amino terminus of Ral GDS, which leads to the dissociation from the inhibitory beta-arrestin and to activation of RalA.…”
Section: A Components Of Exocytosis Signaling Microdomainsmentioning
confidence: 93%
“…Rab proteins found in association with the WPBs are Rab3b Rab3d (Knop et al, 2004), Rab27a (Hannah et al, 2003), Rab3a, Rab15, Rab33a, and Rab37 (Zografou et al, 2012). Rab27a can either inhibit the secretion of WPBs by associating with its effector MyRIP (myosin VIIA and Rab interacting protein), thus anchoring WPBs to actin filaments and keeping them from attaching to the plasma membrane (Nightingale et al, 2009) or activate the secretion of WPBs by associating with an alternate effector, Slp4-a (synaptotagmin-like protein 4), which links the secretory granules to the plasma membrane (Gomi et al, 2005).…”
Section: A Components Of Exocytosis Signaling Microdomainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture of Endothelial Cells, Transfections, InfectionsHUVECs were isolated, cultured, and transfected or infected as described previously (66). Bovine retinal endothelial cells (obtained from VEC Technologies) were cultured on fibronectin-coated dishes, in DMEM supplemented with 10% fetal bovine serum, 4.5 g/liter of glucose, 1% penicillin, 1% streptomycin, 2 mmol/liter of L-glutamine, 25 mmol/liter of Hepes, 20 g/ml of endothelial cell growth supplement, and 50 g/ml of heparin.…”
Section: Methodsmentioning
confidence: 99%
“…HUVECs were isolated, cultured and transfected as previously described (Zografou et al, 2012). Cells were routinely tested for contamination.…”
Section: Cell Treatmentsmentioning
confidence: 99%